AN ANALYSIS OF STUDENTS’ ERRORS IN WRITING SKRIPSI AT THE STUDENTS OF ENGLISH LANGUAGE EDUCATION PROGRAM IN INSTITUT PENDIDIKAN TAPANULI SELATAN - Linda Fauziah Sihombing (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The purpose of this research are to know: 1) the students' ability in writing skripsi, 2) the errors that made by students in writing skripsi. This research use descriptive qualitative method. The data were collected by documentation method. In technique of checking trustworthiness of data the researcher used triangulation. The results of this study are 1) the students ability in writing skripsi at the students of English language education program in Institut Pendidikan Tapanuli Selatan is very good, with the average score 85, 2) the students made errors in writing content is 8 (6.6%), writing organization is 0 (0%), using vocabulary is 3 (2.4%), mastering grammars is 16 (13.2%), and using mechanics is 93 (76.8%). From calculated the data, error of mechanics are the most frequent errors done by students with the percentage 76.8% and the lower percentage is vocabulary with the percentages 3 (2.4%). Keywords: error analysis, writing, skripsi.